L’identité discursive féminine dans le récit manifestant lors des mobilisations citoyennes en Pologne en 2020 - Woch, Agnieszka (Studia Romanica Posnaniensia, 2024)
The present contribution is a corpus-based analysis of protest messages that could be read during demonstrations in Poland against the decision of the Constitutional Court imposing further restrictions on the abortion law in 2020. The corpus is made up of 1000 texts written on placards and banners of the demonstrators, which were photographed and uploaded on newspaper websites or on Facebook between October 22 and November 22. The author examines the slogans with the aim of grasping the discursive identity/identities of protesting women, and reflect on the changing perception of the role of women in the Polish society.